KIAT SUKSES MENDIDIK DAN MENGAJAR PERSPEKTIF KITAB “KAIFA NURABBÎ AULÂDANÂ” KARYA MUHAMMAD IBN JAMIL ZAINU - Sulaiman Jazuli (Institut Agama Islam Darul Ulum Kandangan, 2020)
Education in a family is one of the three center of education. The responsible in educating and teaching in this environment is the parents. This study described the ways to be successful in education and teaching based on the perspective of Kaifa Nurabbî Aulâdanâ book. This research included the library research with the approach of content analysis. The results obtained from this research is composed the material that should be taught to the children and the teaching method. The materials are Introducing the five pillars of Islam, Introducing the Pillars of Faith, Teaching the Truth, Teaching the Prayers, Teaching Qur'an along with the tajwid, Teaching the children the prayer obligation and friday prayer, Teaching the children about the law and the way of prayer, Teaching the children to fast since the age of seven years, Teaching the children to cover the genitalia, Morals and manners teaching, Sirah nabawiyah teaching, Being fair and equate the provision for the children, The ablution and tayammum teaching, Avoiding the children from music and singing, Avoiding the children from the dangers of smoking, Teaching the children to be obedient to both parents, Introducing of jihad and Instilling courage. The methods that can be applied in the teaching materials above is telling story method/Qishah, the Advice and Warning method, Demonstration method/Directly Practice, Exemplary method, Targhib and Tarhib method, and Lecturing Method.